2018
DOI: 10.1519/jsc.0000000000001812
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Effects of a Low-Volume, Power-Type Resistance Exercise Session on Explosive Performance

Abstract: Tsoukos, A, Veligekas, P, Brown, LE, Terzis, G, and Bogdanis, GC. Delayed effects of a low-volume, power-type resistance exercise session on explosive performance. J Strength Cond Res 32(3): 643-650, 2018-This study examined the delayed effects of a power-type training session on explosive performance. Seventeen well-trained male power and team sport athletes (age: 22.7 ± 5.5 years, height: 181 ± 8 cm, body mass: 80.7 ± 8.6 kg, body fat: 9.2 ± 1.7%, 1 repetition maximum (1RM) half-squat: 163 ± 29 kg) performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(96 citation statements)
references
References 41 publications
11
69
0
Order By: Relevance
“…Interestingly, in the present study the power-oriented session appeared to enhance MJ height at 24 h and squat peak power and push-up peak force 48 h after exercise (note that the push-up peak force at 48 h was trivial and unclear compare to baseline, but clearly different between sessions). This is in line with Tsoukos et al (2018), who observed increased CMJ height and RFDmax 24 and 48 h after loaded jump squats (40% of 1RM; 5 × 4 repetitions). In contrast to squat peak power, we observed no such ''supercompensation'' in CMJ, SJ or 20 m sprint (which were all back to baseline at 48 h).…”
Section: Fatigue Vs Potentiation and Supercompensationsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, in the present study the power-oriented session appeared to enhance MJ height at 24 h and squat peak power and push-up peak force 48 h after exercise (note that the push-up peak force at 48 h was trivial and unclear compare to baseline, but clearly different between sessions). This is in line with Tsoukos et al (2018), who observed increased CMJ height and RFDmax 24 and 48 h after loaded jump squats (40% of 1RM; 5 × 4 repetitions). In contrast to squat peak power, we observed no such ''supercompensation'' in CMJ, SJ or 20 m sprint (which were all back to baseline at 48 h).…”
Section: Fatigue Vs Potentiation and Supercompensationsupporting
confidence: 91%
“…In contrast to squat peak power, we observed no such ''supercompensation'' in CMJ, SJ or 20 m sprint (which were all back to baseline at 48 h). Notably, our participants executed a large exercise volume, about three times that of Tsoukos et al (2018), and fatigue mechanisms may have overshadowed most of the supercompensation effects of power exercises. Moreover, we only followed the participants for 48 h, which means that we do not know whether the supercompensation occurred later after the strength-oriented session (e.g., after 72 h).…”
Section: Fatigue Vs Potentiation and Supercompensationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the present study the power-oriented session appeared to enhance MJ height at 24 hours and squat peak power and push-up peak force 48 hours after exercise (note that the push-up peak force at 48 hours was trivial and unclear compare to baseline, but clearly different between sessions). This is in line with Tsoukos et al (2018), who observed increased CMJ height and RFDmax 24 and 48 hours after loaded jump squats (40% of 1RM; 5 x 4 repetitions). In contrast to squat peak power, we observed no such "supercompensation" in CMJ, SJ or 20 m sprint (which were all back to baseline at 48 hours).…”
Section: Fatigue Vs Potentiation and Supercompensationsupporting
confidence: 91%
“…Resistance training (RT) is a common and well-accepted method for the development of muscular strength, power, and hypertrophy. Numerous studies have been undertaken to provide insight into the differences between the frequency of training, [1][2][3][4][5][6] number of muscle groups exercised, 7,8 training volume, [9][10][11][12][13][14] rest intervals, [15][16][17] and velocity of the weight being lifted, 18 although many of these studies have focused on the untrained or novice recreational athlete. 1,3,9,16 In the untrained or novice subject, RT can produce substantial gains in a short period of exposure to a training protocol.…”
mentioning
confidence: 99%